2016
DOI: 10.1016/j.celrep.2016.10.088
|View full text |Cite
|
Sign up to set email alerts
|

mDia and ROCK Mediate Actin-Dependent Presynaptic Remodeling Regulating Synaptic Efficacy and Anxiety

Abstract: Here, we show neuronal inactivation-induced presynaptic remodeling and involvement of the mammalian homolog of Diaphanous (mDia) and Rho-associated coiled-coil-containing kinase (ROCK), Rho-regulated modulators of actin and myosin, in this process. We find that social isolation induces inactivation of nucleus accumbens (NAc) neurons associated with elevated anxiety-like behavior, and that mDia in NAc neurons is essential in this process. Upon inactivation of cultured neurons, mDia induces circumferential actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 40 publications
(45 reference statements)
0
22
0
Order By: Relevance
“…As the actin depolymerization pathway downstream of Sema4D/PlexinB1 signaling via MET is mediated via a reduction of intracellular RhoA activity (Swiercz et al, 2008;Sun et al, 2012), we tested whether stabilization of inhibitory boutons could also be achieved by directly reducing ROCK activity, a well known downstream effector of RhoA (Amano et al, 2010). We found that treatment with the specific ROCK inhibitor Y-27632 (Deguchi et al, 2016) resulted in an increase in the density of stabilizing boutons in our slices (Fig. 7L), without affecting the other subclasses of boutons.…”
Section: Inhibitory Bouton Stabilization By Sema4d Requires Met Activmentioning
confidence: 83%
“…As the actin depolymerization pathway downstream of Sema4D/PlexinB1 signaling via MET is mediated via a reduction of intracellular RhoA activity (Swiercz et al, 2008;Sun et al, 2012), we tested whether stabilization of inhibitory boutons could also be achieved by directly reducing ROCK activity, a well known downstream effector of RhoA (Amano et al, 2010). We found that treatment with the specific ROCK inhibitor Y-27632 (Deguchi et al, 2016) resulted in an increase in the density of stabilizing boutons in our slices (Fig. 7L), without affecting the other subclasses of boutons.…”
Section: Inhibitory Bouton Stabilization By Sema4d Requires Met Activmentioning
confidence: 83%
“…Although tamoxifen has been used in mouse models for a long time, the effects of tamoxifen have not been researched . In the isolation model, isolation can result in hyperactivity and depression .…”
Section: Discussionmentioning
confidence: 99%
“…All the above mentioned results were in mice that were not subjected to mouse models or mutagenesis. In the literature, many experiments are designed to make mice into animal models before or after tamoxifen administration . Therefore, we designed protocols to explore whether tamoxifen could promote or prevent behavioral alterations after the mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in our model when a microtubule is depolymerizing, the Rho protein is activated leading to a Rac inactivation. The reaction terms then read: (15) with, τ Rac→Rac the intrinsic activation rate, τ Rac→Rac the inactivation rate, γ Rac , K Rac parameters for the positive feedback. The function k 0 is used to know if a microtubule is polymerizing or not:…”
Section: Reaction Termsmentioning
confidence: 99%
“…Rho regulates actomyosin formation through mammalian homolog of Diaphanous (mDia) and Rho-associated coiled-coil-containing kinase (ROCK) [37]. The mDia protein promotes actin nucleation and polymerization [15] while ROCK activates myosin light chain and cooperates with mDia to form actomyosin bundles and generate contractility [37]. In this paper, Rho is assumed to activate ROCK at the rear of the cell to regulate actomyosin contractility.…”
mentioning
confidence: 99%